The Crux of Refugee Resettlement : Rebuilding Social Networks. - Adhikari, Surendra Bir (Crossing Borders in a Global World: Applying Anthropology to Migration, Displacement, and Social Change., 2018)
The Crux of Refugee Resettlement reenvisions third-country resettlement, with a focus on the social networks generated by refugees. Each contributor uses ethnography to highlight refugee voices and experiences. This collection showcases the ways in which community-based solutions rebuild social networks and counteract the alienating conditions of resettlement.